Empowering Voices: Education’s Role in Bridging Women’s Domestic and Public Decision-Making Divide in Malakand Division, Pakistan - Umar Daraz; Farman Ali; Muhammad Ashfaq Khan; Jahan-Ul-Mulk; Zakir Hussain (Dialogue Social Science Review (DSSR), 2025)
Education plays a pivotal role in empowering women and fostering their development, acting as a catalyst for autonomy and self-sufficiency in decision-making across domestic and public spheres. Our study delves into the transformative impact of education on women's decisional empowerment, unraveling its essence within family and public settings. Conducted in the vibrant region of Malakand Division, Khyber Pakhtunkhwa, Pakistan, where women's education has witnessed remarkable progress in recent years, the research sheds light on how education empowers women, leading to enhanced empowerment in various aspects of their lives. A sample of 384 participants was selected using stratified random sampling (proportionate method), and a questionnaire was employed as the primary tool for data collection. Employing a pure quantitative approach, the data was analyzed using SPSS (version 20). The findings strongly affirm that education stands as a powerful tool in fostering women's empowerment, significantly influencing their decision-making processes within both the home and the public domain.